2005
DOI: 10.1103/physrevlett.94.056102
|View full text |Cite
|
Sign up to set email alerts
|

Boundary Slip on Smooth Hydrophobic Surfaces: Intrinsic Effects and Possible Artifacts

Abstract: We report an accurate determination of the hydrodynamic boundary condition of simple liquids flowing on smooth hydrophobic surfaces using a dynamic surface force apparatus equipped with two independent subnanometer resolution sensors. The boundary slip observed is well defined and does not depend on the scale of investigation from one to several hundreds of nanometers, nor on shear rate up to 5 x 10(3)s(-1). The slip length of 20 nm is in good agreement with theory and numerical simulations concerning smooth n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

39
424
1
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 430 publications
(474 citation statements)
references
References 34 publications
39
424
1
10
Order By: Relevance
“…The results above, together with experiments showing dependence of slip on the absolute value of the pressure [161], and spatially-varying velocity fields [163], hint at the possibility of flow over surface-attached gas pockets or bubbles (see also the discussion in [101]). Recent results in [38] also point at the possibility of flow over gas pockets associated with the contamination of hydrophobic surfaces by nanoparticles. We also note that the group of Steve Granick reported a contamination of their previous ostensibly smooth mica surfaces by platinum nanoparticles [104], possibly affecting some of their experimental results in [192,193,194,195].…”
Section: Dissolved Gas and Bubblesmentioning
confidence: 99%
See 1 more Smart Citation
“…The results above, together with experiments showing dependence of slip on the absolute value of the pressure [161], and spatially-varying velocity fields [163], hint at the possibility of flow over surface-attached gas pockets or bubbles (see also the discussion in [101]). Recent results in [38] also point at the possibility of flow over gas pockets associated with the contamination of hydrophobic surfaces by nanoparticles. We also note that the group of Steve Granick reported a contamination of their previous ostensibly smooth mica surfaces by platinum nanoparticles [104], possibly affecting some of their experimental results in [192,193,194,195].…”
Section: Dissolved Gas and Bubblesmentioning
confidence: 99%
“…The surface is said to be hydrophobic if θ c > 90 • , and in that case the nucleation of small bubbles in the liquid should occur preferentially on the surface. Slip has been measured for systems in complete wetting [17,18,67,68,125,126] and partial wetting [9,16,29,31,32,33,34,38,39,40,67,87,88,68,108,116,150,162,163,178,192,194,195]. The amount of slip has usually been found to increase with contact angle, either systematically (e.g., [192]) or only for non-polar liquids [31].…”
Section: Wettingmentioning
confidence: 99%
“…For molecular interactions between neutral solutes and a solid L is very small, e.g. ∼ 0.3 nm, so with b ∼ 20 − 30 nm for water on hydrophobic substrates [5,6], the amplification factor can be up to 100 ! Formal general argument -We now generalize this result.…”
mentioning
confidence: 99%
“…Recent efforts in this domain have concluded that with a clean "solvophobic" surface chemistry one can reach slip lengths up to a few ten nanometers [6], but not much more unless topographic structures are specifically engineered [7].…”
mentioning
confidence: 99%
“…Details of these experiments can be found in Cottin-Bizonne et al (2005). Figure 2 shows the experimental results for each system.…”
Section: Surface Force Measurementsmentioning
confidence: 99%